Object, Room, Dwelling: Material Culture and the Indigenous City in the Colonial Andes. - Mangan, Jane E. (Hispanic American Historical Review, 2025)
This article analyzes objects and abodes to further the understanding of lived experience in colonial Andean cities. It builds on existing scholarship on women's dress by analyzing household objects and even domestic structures themselves. Seeking to elaborate on Indigenous and mestiza women's experiences of the colonial city, the article draws primarily on notarial and judicial records for Arequipa, La Plata (today Sucre, Bolivia), and Potosí between the late 1500s and the mid-1600s. The essay opens with a discussion of the topu (Indigenous dress pin), moves to study the entirety of inventories held by specific city dwellers, and, finally, considers the significance of the domestic structure in terms of Indigenous urban experience. Through evidence of material culture and built environment, the article argues, we can gain a deeper understanding of the Indigenous cultural, social, and architectural identity of colonial cities in the face of Spanish presence.